International drug control : consensus fractured - Bewley-Taylor, David R. (Cambridge University Press CambridgeGB, 2012)
Presents the author's observations nuanced by information, insights and practical perspectives of over fifty formal interviews conducted at the Commission on Narcotic Drugs in Vienna. Examines the national, and sub-national, supra-national and UN level processes behind, as well as subsequent reactions to, regime transformation since 1998. Charts the increasing normalisation of the harm reduction approach. Shows how many (particularly European) Parties to the UN Conventions have embraced a range of interventions that deviate to varying degrees from the regime's prohibitive norm.